2019
DOI: 10.1037/bar0000097
|View full text |Cite
|
Sign up to set email alerts
|

The impact of training in functional analytic therapy on therapists’ target behavior.

Abstract: The proposed mechanism of action in Functional Analytic Psychotherapy (FAP) is therapist-contingent responses to client in-session behavior that parallels out-of-session problematic behavior. In theory, these responses shape adaptive behaviors that generalize into the client's daily life (Tsai et al., 2009). Therefore, the therapist's response repertoire must be ripe with interpersonally effective responses to model and shape client behavior. Thus, trainings in FAP were designed not only to equip therapists wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…The main reasons for exclusion were lack of quantitative measures of clinical outcomes for group studies ( n = 15) and lack of baseline measures for SCD ( n = 6). We found one duplicate record reporting the same study data (Knott, 2014; Knott et al, 2019) and decided to include the first record because it reported more data…”
Section: Resultsmentioning
confidence: 99%
“…The main reasons for exclusion were lack of quantitative measures of clinical outcomes for group studies ( n = 15) and lack of baseline measures for SCD ( n = 6). We found one duplicate record reporting the same study data (Knott, 2014; Knott et al, 2019) and decided to include the first record because it reported more data…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, online experiential training on alliance building in functional analytic psychotherapy (FAP; Ackerman & Hilsenroth, 2003), including didactics, interactive activities, and practice between training sessions, demonstrated positive therapist outcomes. Following FAP training, therapists had gained knowledge and had shown improvements in self-reported and observer-rated levels of competency (Kanter et al, 2013;Maitland et al, 2016), possibly impacting therapists' skills in their subsequent clinical work (Knott et al, 2019). Similarly, an online tutorial followed by live remote observation of clinical skills via videoconference resulted in improved therapists' knowledge and competence (Kobak et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies (Kanter et al, 2013;Keng et al, 2017;Knott et al, 2019;Maitland et al, 2016) assessed the effects of training in functional analytic psychotherapy (FAP), a behavioral treatment that emphasizes the development of an intimate and intense therapy relationship as the vehicle for client change. FAP is part of the third wave of behavioral treatments focused on mindfulness, acceptance, and constructive change.…”
Section: Training For Behavioral Therapiesmentioning
confidence: 99%